PHYSICAL MODELING OF SKIRT BREAKWATERS TO MEASURE THE EFFECTIVENESS OF THE DISSIPATION MECHANISM ON SKIRTS - Ali Wibowo, Azis
Gravity-type breakwaters such as the rubble mound type are ineffective in intermediate-depth (transitional) (?/10<kh<?) and deep water (kh>?) due to high construction cost. In intermediate-depth and deep waters, the skirt-type breakwater is one of the best alternatives due to the low construction cost because the breakwater structure is consists of a pile at the bottom part and a skirt wall in the upper part of the structure. To investigate the effectiveness of the skirt type breakwaters, 2-dimensional physical modeling in wave flume and 3-dimensional physical modeling in wave basin conducted at the Ocean Engineering Laboratory at Bandung Institute of Technology, Indonesia. Three dimensional (3D) and two dimensional (2D) physical modeling is carried out on the Single Chamber Skirt Breakwater (SCSB) and Multi Chamber Skirt Breakwater (MCSB) structures. The relationship between the parameter of Transmission Coefficient (CT) and Reflection Coefficient (CR) with the environmental and structural parameters are examined to obtain the optimum performance of the breakwater structure in intermediate-depth (transitional) and deep waters. Transmission Coefficient Analysis(CT) is investigated by comparing the value of the transmitted wave (HT) with the incident wave (HI), while the Reflection Coefficient (CR) analysis is investigated by comparint the reflected wave energy (ER) with the incident wave energy (EI). The Goda and Suzuki method (1976) used to separate the incident waves and reflected wave from the composite waves in front of the structure. The results of the analysis are in the form of non-dimensional graph and empirical equations describing the relationship of CT and CR with efective depth (kh), wave steepness (HI/L), relative draft (s/h) and relative curtain distance (Lc/h). The physical modeling of PGTG and PGTJ concludes that this breakwater effective for application in transitional waters and deep waters. There are differences in the results of KT values and KR values in 2D and 3D physical modeling, so 3D effects need to be considered in the design of breakwater structures.